Pengaruh Trouble Ticketing System Terhadap Kepuasan Pelanggan (Studi Kasus PT Solusindo Bintang Pratama Batam Jasa Internet Service Provider/ISP) - Rika Harman (Computer Based Information System Journal, 2014)
Long term investment in information technology systems leads to the cost advantage of low-cost leadership. Providing online customer service makes the company's operations become easier and efficient and one form of online services is web-based system. Trouble Ticketing System is a web-based system that is commonly used in dealing with any customer complaints against interruption or the decrease of quality of the internet perceived. In addition, this system can also handle upgrade or downgrade requests, mutation of the customer and receive customer complaints report through e-mail, telephone and client applications on the system. In this case, a support/csc plays an important role in controlling every activity on the system. The main task of this support/csc is to create trouble ticket or any other requests ticket, completing the task to the first level corresponding to the SOP and run interference escalation to a higher level, until the trouble ticket is completely processed. For those who work in the network field or network administrator, Trouble Ticketing System is an application that is also called a trouble report, a mechanism used by a company or organization to track or to detect report and resolution of various types of problems. Trouble Ticketing System contains complaints and requests for support/hepdesk, and is equipped with ticket escalation feature to the company management. By this, any form of customers complaints and request can be responded quickly and in turn will facilitate the management internal policy or decision-making.